Particle acceleration by twisted laser beams - Mendonça, J.T.; Vieira, J.; Willim, C.; Fedele, R. (Frontiers in Physics, 2022)
We consider particle acceleration in plasmas, using twisted laser beams, or beams with orbital angular momentum. We discuss different acceleration processes using two LG laser modes, which include donut wakefield, beat-wave and self-torque acceleration, and compare the respective prop- erties. We show that a self-torque configuration is able to produce azimuthal acceleration and can therefore be considered as an alternative method produce helical electron beams.